2020
DOI: 10.2147/ndt.s269835
|View full text |Cite
|
Sign up to set email alerts
|

<p>No Associations of Psychological Symptoms and Suicide Risk with Disaster Experiences in Junior High School Students 5 Years After the 2011 Great East Japan Earthquake and Tsunami</p>

Abstract: Introduction: Natural disasters such as earthquakes can cause substantial damage and trauma, especially to children. The aim of this study was to examine the effects of disaster experience on psychological symptoms, suicide risk, and associated factors in junior high school students 5 years after the Great East Japan Earthquake (GEJE). The hypothesis of this study was that psychological symptoms and suicide risk of junior high school students are associated with disaster experience. Methods: A cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…These studies were conducted in the three-year period following the GEJE [ 20 , 21 , 22 ]. However, one study that targeted junior high school students showed no significant association with disaster-related experiences, and this was conducted five years after the disaster, indicating that the psychological effects of the disaster may have subsided over time [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…These studies were conducted in the three-year period following the GEJE [ 20 , 21 , 22 ]. However, one study that targeted junior high school students showed no significant association with disaster-related experiences, and this was conducted five years after the disaster, indicating that the psychological effects of the disaster may have subsided over time [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The children were asked to self-administer the following questionnaires to assess their clinical status: Kidd-KINDL R (8–13 years) or Kiddo-KINDL R (14–17 years) ( 24 , 25 ), the Depression Self-Rating Scale for Children (DSRS-C) ( 26 ), the Spence Children's Anxiety Scale (SCAS) ( 26 , 27 ), and a visual analog scale (VAS) for temporary mood status in terms of percentages of the best imaginable state ( 28 , 29 ). The parents assessed the maladaptive behaviors of their children using the Child Behavior Checklist (CBCL) ( 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…24,25 The National Center for Global Health and Medicine conducted city-wide longitudinal surveys of kindergarten, elementary school, and junior high school children, observing the recovery course of traumatic symptoms. [26][27][28][29][30][31] The Department of Health Informatics and Public Health, Tohoku University School of Public Health, conducted longitudinal surveys of the residential registry for Ajishima, Ogatsu, Oshika, and Ishinomaki City, as well as residents who were living in prefabricated temporary housing in Wakabayashi-ku, Sendai City, and Miyagi Prefecture. The study indicated that psychological distress was associated with an increased risk of musculoskeletal pain among survivors 32 and functional disability among elderly survivors of a natural disaster.…”
Section: Clinical Neurosciencesmentioning
confidence: 99%
“…The Health and Life Revival Council in Ishinomaki District conducted cross‐sectional household surveys, highlighting the importance of economic factors for the affected communities and emotional support, especially for the elderly disaster victims 24,25 . The National Center for Global Health and Medicine conducted city‐wide longitudinal surveys of kindergarten, elementary school, and junior high school children, observing the recovery course of traumatic symptoms 26–31 …”
Section: Advances In Mental Health Disaster Response After the Gejementioning
confidence: 99%